Strategi Diversifikasi Produk Bank Syariah untuk Jangkauan Pasar yang Lebih Luas - Khotimah, Husnul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyse the product diversification strategy of Islamic banks in order to expand market reach in Indonesia. Although Islamic banks have great potential, there are still many people who choose conventional banks due to a lack of knowledge and understanding of Islamic bank products. Through a qualitative approach, this study identifies the various products offered by Islamic banks, including investment and financing products, as well as the importance of regulatory support from the government. The results show that proper product diversification can improve the competitiveness of Islamic banks and attract more customers. This research suggests that Islamic banks should continue to innovate and conduct educational campaigns to increase public awareness about the benefits of Islamic banking.